ANALISIS PELAYANAN PUBLIK PASCA REFORMASI DALAM TINJAUAN SOSIOLOGI - Frendly Albertus; Wesley Hutasoit (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2020)
Since the events of the reforms in 1998, changes in the public service system have been the main objective when the crisis hit the economy and politics. But instead of reform in the service of the public is still far from expectations compared with the reform of the political and reform of laws. Peoples who is also a subject in the service of the public to the process of bureaucratic administration of the public also undartake efforts to repair. In this study, we try to provide preliminary descriptions of post-reform public service analysis in the Sociology review